Penerapan Penggunaan Antibiotik Bersertifikasi Halal Pada Pasien Anak Dengan Diare Akut Di RSD K.R.M.T Wongsonegoro - Purnami, Islina Dewi; Nugrahaeini, Atma Rulin Dewi; Aprilla, Trifani (Sultan Agung Islamic University of Semarang, 2023)
Background : The use of antibiotics in accordance with the antibiotic resistance control program in pediatric patients with acute diarrhea and halal certification on antibiotics. The purpose of this study was to known the implementation of halal certification antibiotics according to antibiotic resistance control program in pediatric patients with acute diarrhea at RSD K.R.M.T Wongsonegoro. Methods: The research method used was a retrospective descriptive approach by collecting data from medical records in pediatric patients with acut diarrhea. The population in this study were pediatric patients with acute diarrhea who were hospitalzed at RSD K.R.M.T Wongsonegoro, with inclusion criteria being pediatric patients diagnosed with acute diarrhea in inpatient care. Data taken from medical records include: age, gender, name of antibiotik, route of administration, then the use of antibiotic is calculated by the DDD (Defined Daily Dose/100 patient-days) formula, for halal certification of antibiotics through the MUI website then calculate the percentage. Results: the number of antibiotic used in the treatment of acute diarrhea in children 36 pediatric patients ware ceftriaxone antibiotic as much as 24.57, Cefotaxime 5.47, oral metronidazole 4.52, amoxicillin 1.31, parenteral metronidazole 1.27 and 0,1 cefixme either orally or parenterally. While the percentage of antibiotics that have halal certification is 100%. Conclusion: Antibiotic with the highest use was cefotaxime 5.57 while the lowest was cefixime 0.1. for all antibiotics in the RSD K.R.M.T Wongsonegoro, they have been certified halal. Keywords: Acute Diarrhea; Antibiotic; Halal Certification; Pediatric Patient; Resistance